Embracing complexity with systems thinking in general practitioners' clinical reasoning helps handling uncertainty. Issue 5 (16th February 2021) - Stolper, Erik; Van Royen, Paul; Jack, Edmund; Uleman, Jeroen; Olde Rikkert, Marcel
Abstract: Clinical reasoning in general practice is increasingly challenging because of the rise in the number of patients with multimorbidity. This creates uncertainty because of unpredictable interactions between the symptoms from multiple medical problems and the patient's personality, psychosocial context and life history. Case analysis may then be more appropriately managed by systems thinking than by hypothetic‐deductive reasoning, the predominant paradigm in the current teaching of clinical reasoning. Application of "systems thinking" tools such as causal loop diagrams allows the patient's problems to be viewed holistically and facilitates understanding of the complex interactions. We will show how complexity levels can be graded in clinical reasoning and demonstrate where and how systems thinking can have added value by means of a case history.